1995
DOI: 10.1193/1.1585829
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Challenge: Report on the Performance of State Bridges in the Northridge Earthquake

Abstract: Bridges affected by the Northridge earthquake were examined to evaluate the performance of Caltrans bridges, retrofit and peer review programs, and technical procedures. All structures in the region of strong shaking that had been retrofitted since 1989 performed adequately; if the seven bridges that collapsed had been retrofitted, they would be expected to have survived with little damage. The bridges subjected to strong shaking that had been constructed or retrofitted to current Caltrans criteria had, at mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In the meantime, land use regulations, urban planning and safety policies regarding earthquake disasters are typically based on previous evidence or knowledge, rather than on future possibilities. These difficulties make it much harder to plan for seismic disasters than for any other natural hazard (Steinbrugge, 1982;California Department of Conservation, 1988;Palm, 1989;Berke and Beatley, 1992;Housner and Thiel, 1995;Kovach, 1995;Stallings, 1995).…”
Section: Clustering and Polycentricitymentioning
confidence: 99%
“…In the meantime, land use regulations, urban planning and safety policies regarding earthquake disasters are typically based on previous evidence or knowledge, rather than on future possibilities. These difficulties make it much harder to plan for seismic disasters than for any other natural hazard (Steinbrugge, 1982;California Department of Conservation, 1988;Palm, 1989;Berke and Beatley, 1992;Housner and Thiel, 1995;Kovach, 1995;Stallings, 1995).…”
Section: Clustering and Polycentricitymentioning
confidence: 99%
“…In summary, the critical issue in retrofitting program is not lack of technical design and standard or practical issues instead, prioritization methods are required to be improved. For instance, five out of seven bridges that collapsed in the Northridge earthquake (1994) had been scheduled as requiring retrofit, and two other bridges had been identified as not requiring retrofit in the first stage (Housner, Thiel Jr 1995;Yashinsky, Karshenas 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In conventional design, such an abutment is proportioned to resist the active earth loading for safety against outward sliding and overturning in earthquakes. Past studies [5,6] found that during earthquakes most abutments mainly behaved as rigid walls in tilting, without sliding at the base.…”
Section: Introductionmentioning
confidence: 99%